A case study analysis to examine motorcycle crashes in Bogota, Colombia. (February 2015) - Jimenez, Adriana; Bocarejo, Juan Pablo; Zarama, Roberto; Yerpez, Joël
Abstract: Introduction: Contributory factors to motorcycle crashes vary among populations depending on several aspects such as the users' profiles, the composition and density of traffic, and the infrastructure features. A better understanding of local motorcycle crashes can be reached in those places where a comprehensive analysis is performed. This paper presents the results obtained from a case study analysis of 400 police records of accidents involving motorcycles in Bogota. Method: To achieve a deeper level of understanding of how these accidents occur, we propose a systemic approach that uses available crash data. The methodology is inspired by accident prototypical scenarios, a tool for analysis developed in France. Results: When grouping cases we identified three categories: solo motorcycle accidents, motorcyclist and pedestrian accidents, and accidents involving a motorcycle and another vehicle. Within these categories we undertook in-depth analyses of 32 groups of accidents obtaining valuable information to better comprehend motorcyclists' road crashes in a local context. Recurrent contributory factors in the groups of accidents include: inexperienced motorcyclists, wide urban roads that incite speeding and risky overtaking maneuvers, flowing urban roads that encourage high speed and increased interaction between vehicles, and lack of infrastructure maintenance. Practical Applications: The results obtained are a valuable asset to define measures that will be conveniently adapted to the group of accident on which we want to act. The methodology exposed in this paper is applicable to the study of road crashes that involve all types of actors, not only the motorcyclists, and in contexts different than those presented in Bogota. Highlights: The proposed methodology is an initiative for developing countries to analyze road crashes. Despite the limitations in the road accident data, the methodology contribute to better understand how crashes are occurring. This understanding will facilitate the formulation of actions to reduce frequency and severity road crashes in these countries. 32 accident groups and 53 accident factors were identified. It shows the complexity of the motorcycle crashes in Bogota.